2004
DOI: 10.1002/cncr.11937
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose tamoxifen and sulindac as first‐line treatment for desmoid tumors

Abstract: BACKGROUND.Desmoid tumors are mesenchymal nonmetastasizing neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
221
3
10

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(239 citation statements)
references
References 38 publications
(24 reference statements)
4
221
3
10
Order By: Relevance
“…Patients with familial adenomatous polyposis (FAP) syndrome have a 1000-fold increased risk of developing desmoid tumor, and account for approximately 2% of all cases. 6 The observation that some fibromatosis cases, particularly abdominal fibromatosis, occur in association with pregnancy has suggested that these tumors might be hormonally responsive. Women have over a threefold greater risk of developing fibromatosis than men 6 and tend to have more rapidly growing tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with familial adenomatous polyposis (FAP) syndrome have a 1000-fold increased risk of developing desmoid tumor, and account for approximately 2% of all cases. 6 The observation that some fibromatosis cases, particularly abdominal fibromatosis, occur in association with pregnancy has suggested that these tumors might be hormonally responsive. Women have over a threefold greater risk of developing fibromatosis than men 6 and tend to have more rapidly growing tumors.…”
Section: Discussionmentioning
confidence: 99%
“…6 The observation that some fibromatosis cases, particularly abdominal fibromatosis, occur in association with pregnancy has suggested that these tumors might be hormonally responsive. Women have over a threefold greater risk of developing fibromatosis than men 6 and tend to have more rapidly growing tumors. Anecdotal cases have involuted with the withdrawal of hormonal replacement therapy, and in familial polyposis coli patients the use of contraceptives increases the risk of developing abdominal fibromatosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is found to cause partial response to the tumour or stabilizes disease process and prevents progression [9]. In addition to Tamoxifen, high dose Sulindac has also been used as it inhibits beta catenin signaling and has been found to have additive effect to Tamoxifen [9,10]. A combination of vincristine, actinomycin D and cyclophosphamide has also been used in few selective cases not responding to hormonal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These agents are reportedly shown to be effective in 15-30% of desmoid tumor cases (22,23). Since the desmoid tumor of case 1 patient markedly shrank after low-dose D-D therapy with the aid of sulindac and tamoxifen, we cannot deny the possibility that additional administration of these supplementary agents might also be of importance for treating desmoid tumors.…”
Section: A B B B a Discussionmentioning
confidence: 99%